Single-cell transcriptomes and T cell receptors of vaccine-expanded apolipoprotein B-specific T cells - Nettersheim, Felix Sebastian; Ghosheh, Yanal; Winkels, Holger; Kobiyama, Kouji; Durant, Christopher; Armstrong, Sujit Silas; Brunel, Simon; Roy, Payel; Dileepan, Thamotharampillai; Jenkins, Marc K.; Zajonc, Dirk M.; Ley, Klaus (Frontiers in Cardiovascular Medicine, 2023)
Atherosclerotic cardiovascular diseases are the major cause of death worldwide. CD4 T cells responding to Apolipoprotein B (ApoB), the core protein of most lipoproteins, have been identified as critical disease modulators. In healthy individuals, ApoB-reactive (ApoB+) CD4 T cells are mostly regulatory T cells (Tregs), which exert anti-inflammatory effects. Yet, they may obtain pro-inflammatory features and thus become proatherogenic. Evidence from animal studies suggests that vaccination against certain major histocompatibility complex (MHC) II-binding ApoB peptides induces an expansion of ApoB+ Tregs and thus confers atheroprotection. To date, in-depth phenotyping of vaccine-expanded ApoB+ T cells has not yet been performed. To this end, we vaccinated C57BL/6J mice with the ApoB-peptide P6 (ApoB978-993 TGAYSNASSTESASY) and performed single-cell RNA sequencing of tetramer-sorted P6+ T cells. P6+ cells were clonally expanded (one major, two minor clones) and formed a transcriptional cluster distinct from clusters mainly containing non-expanded P6+ and P6- cells. Transcriptomic profiling revealed that most expanded P6+ cells had a strong Treg signature and highly expressed genes mediating suppressive function. Yet, some expanded P6+ cells only had a residual Treg signature and expressed genes related to T helper 1 (TH1) cells, which are proatherogenic. Modeling the T cell receptor (TCR) and P6:MHC-II interaction showed that only 3 amino acid residues in each the α and β chain contact the P6 peptide in the MHC-II groove and thus determine the specificity of this TCR to P6. Our data begin to reveal the vaccination-induced response to an ApoB epitope.